PERSEPSI MAHASISWA SEMESTER VII PGSD TENTANG PELAKSANAAN PROGRAM PENGALAMAN LAPANGAN (PPL) OLEH FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UMS TAHUN AKADEMIK 2013/2014 - Suwarno, Suwarno Suwarno; Ariyanto, Wahyu Doko (Universitas Muhammadiyah Surakarta, 2014)
This study aimed to describe the implementation of PPL (Professional and Teaching Practiceat School) for PGSD FKIP UMS students; PGSD students’ perception towards PPL.This research is descriptive with qualitative approach. Sources of data in this study arestudents, mentor teachers coordinator, and lecturers as PPL supervisor. Data collectiontechniques used were questionnaires, interviews, and documentation. The questionnairewere obtained from 60 students to determine VII semester PGSD FKIP UMS students’perceptions about PPL 2013. Interviews were conducted to students who had attendedthe PPL, coordinator of mentor teachers, and lecturers.. Data analysis techniques performedinteractively. The validity of the data used triangulation technique. Based on theresults of research conducted by researchers at the school with good quality, medium, andregular shows that the number of 35 or 58.33 % of the students expressed that one poin tobe improved is in terms of the time of registration. A number of 50 or 83.33 % of thestudents stated that in the partner schools do not have science labs and learning of mathematicsas a suggestion. A total of 60 or 100 % of students stated that the performance ofmentor teachers’ coordinator in carrying out the task was quite good. Some 21 or 31 % ofstudents stated that some mentor teachers were still using conventional learning strategiesor unable to model an active and innovative teachers for the student-teachers. Atotal of 40 or 66.67 % of the students stated that the performance of the supervisors needsto be improved, especially to guide students in preparing and developing student-teachers’learning program at school and in assisting them writing final report of PPL. A number of41 or 68.33 % of the students stated that it is mandatory to give a memento to the partnerschool. Some 57 or 95 % of students stated that students are required to have teachingpractice exams at partner school. It was concluded that the good cooperation betweenthe organizers of the PPL, students, supervisors, teacher and mentor teacher coordinatorto facilitate the implementation of the PPL .